Challenges and issues of decentralized agriculture service at the VDC level: experiences from Okhaldhunga District - Jaishi, M.; Allen, R.; Sahi, L. (Journal of the Institute of Agriculture and Animal Science, 2018)
Decentralized management of natural resources has the potential to solve the twin problems of Nepalese society which are poverty and poor governance. An important focus of the Local Self Government Act (LSGA) of 1999 is to develop a local self-governance system and local leadership through which local bodies (LBs) make decisions on matters affecting their daily needs and livelihoods. Through the capacity building of local bodies, there is an ample opportunity to boost effective decentralized agriculture service provision at the VDC level. The objective of this paper is to provide basic understanding of the challenge and issues felt during implementation of VDC-level decentralization in the agricultural sector. A review of documents describing extension reforms and experiences was conducted in support of this study. Experience to date shows a great willingness of rural people to take responsibility for local development and to receive appropriate training to improve their management capability. LBs and development partners can assist in capacity building and further strengthen such local bodies to mitigate weaknesses. However, there remain challenges and issues to provide effective agricultural services in enhancing the livelihoods of the poor and to the promotion of more market-led production system. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, Page: 79-90